Development of prototype killed vaccine against Staphylococcus aureus mastitis in dairy cows - Hambali, Idris Umar (2018)
Mastitis is the inflammation of the udder in dairy cows and other species which is caused by bacteria, virus, fungi, toxins, physical and other chemical factors. Despite the continued use of antibiotics in treating mastitis in dairy cows, there are reports of occurrence of mastitis in dairy farms in Malaysia due to antibiotic failures. Therefore, the present study opined to develop a prototype killed mastitis vaccine using local Malaysian isolate of S. aureus with a view that it may assist in reducing the burden of mastitis among cows in Malaysia. The current study was therefore designed and experimented on heifer and lactating Friesian cows models. Killed vaccine was developed using the Malaysian local isolate of S. aureus and adjuvated with Aluminium potassium sulfate. A preliminary proof of concept study using the heifer cows was carried out where four different concentrations of the vaccines were prepared to contain 106, 107, 108 and 109 cfu/ml of S. aureus so as to evaluate the best concentration in terms of evoking immune response in cows. Thirty heifer cows were grouped into 5; group A (control), group B (106 cfu/ml), group C (107 cfu/ml), group D (108 cfu/ml) and group E (109 cfu/ml). The experimental animals were vaccinated intramuscularly with 2 ml of the prepared vaccine and observed for acute and chronic responses post vaccination at 0, 3, 24 hours and at weeks 1, 2, 3 and 4 post vaccination. The vaccination with killed S. aureus vaccine in heifer cows was observed to induce significant immune response more in group D (108 cfu/ml) as compared to other groups. The preliminary study assessed the periodic effect of the developed prototype vaccine groups on both the vital signs and immune regulators. The vital signs examined were rectal temperature, heart rate and respiratory rates, while the immune parameters examined were IL-10, SAA, IgM and IgG. In the present study SAA was significantly different in groups D and E post vaccination (PV). The IL-10 concentrations indicated a statistical significant difference in group D and C PV. IgM in serum of the heifer at PV indicated a statistical significant increase in Groups B and C. Serum IgG at PV indicated a statistical significant difference in Group E and D. The IgG concentrations of Group D tend to be significant from its onset to the end of the experiment. This degree of potency evoked by group D suggested that this vaccine group (108 cfu/ml) could confer immunity compared to other vaccine groups and hence can be considered as capable of evoking immunity against S. aureus challenge in cows. This vaccine group 108 cfu/ml, became the vaccine candidate of choice for the next phase of trial on lactating Friesian dairy cows. In this trial, six lactating Friesian cows were grouped into three groups with two cows each in group C (108 cfu/ml vaccine), group B (positive control) and group A (negative control). During primary vaccination, booster vaccination and S. aureus challenge phases of the experimental trial, variables like clinical manifestation of mastitis, cytokine, APPs, antibodies and tissue histopathology were evaluated. The experimental animals were vaccinated intramuscularly with 2 ml of the prepared vaccine and observed for acute and chronic responses at post primary vaccination (PPV) (at 0, 3, 8, 12, 24 hours and at weeks 1, 2 PPV), at post booster vaccination phase (PB) (at 0, 3, 8, 12, 24 hours PB) and at post S. aureus challenge phases (PC) (at 0, 3, 8, 12, 24 hours and at weeks 1, 2 PC). The rectal temperature of the vaccinated lactating Frisian cows was significantly increased following primary vaccination and booster doses as well as slightly following bacterial challenge, but, the rectal temperature of the positive control group was found to be non-significant following primary vaccination and booster doses but significantly increased following bacterial challenge. The heart rates of lactating Friesian cows in the vaccinated group were increased significantly post vaccination. The heart rates in the positive control group were found to have increased significantly post challenge with S. aureus. The increased heart rate post vaccination and challenge could be a compensatory mechanism to cope with the increased rectal temperature. In this present vaccine trial on lactating Friesian cows, palpation revealed the enlargement of the teat, mammary gland and supramammary lymph nodes especially from the positive control group following S. aureus challenge at weeks 1 and 2 post challenge. The absence of these enlargements in the vaccinated group following challenge with S. aureus suggested a good prognosis of the efficacy of the killed S. aureus vaccine against mastitis in cows. The killed S. aureus vaccine was unable to confer a 100% immunity to the vaccinated group as one out of the eight quarters from the vaccinated group was swollen at week 1 post challenge which later reduced in size and resumed milking with no pain at week 2 post challenge. There was evidence of significant increase in IL-10 concentration in vaccinated group PPV, PB and PC. There was also a significant increase in IL-12 concentration in the vaccinated group PPV, PB and PC. The findings further demonstrated that IgM concentrations of the vaccinated group was significantly high during the PPV, PB and P. The IgG concentrations of the vaccinated group was high during the acute phase PB and PC. IgA was also assayed from the vaccinated groups which was higher during the PB and PC. Grossly, the positive control group developed a significant inflammatory sign in the teat and mammary gland following challenge with S. aureus. Mammary gland incision revealed that the parenchyma of the positive control group had a clotted thick mastitic milk and inflammatory products blocking the milk duct. Histopathological study of the mammary gland, teat, GALT, spleen and thymus in the positive group indicated inflammatory cell infiltration, congestion, degeneration, traces of oedema. This current study provided a dependable vaccine candidate against S. aureus mastitis and the detailed involvement of the vital signs, SAA, Hp, IL-10, IL-12, IgM, IgG, IgA, mammary gland, supramammary lymph node, spleen, thymus and GALT. Based on these findings, it can therefore be concluded that the study had further demonstrated the efficacy of the prototype S. aureus vaccine against S. aureus mastitis in cows.